Comparison of the success of inferior alveolar nerve anesthesia in the mandibular first molars with symptomatic irreversible pulpitis using two anesthetic solutions of prilocaine and mepivacaine: A randomized controlled clinical trial - Mahsa Eskandarinezhad; Negin Ghasemi; Parisa Rostami; Amir Ardalan Abdollahi (Wolters Kluwer Medknow Publications, 2023)
Background: This study aimed to compare the success rate of inferior alveolar nerve (IAN) anesthesia in the mandibular first molars with symptomatic irreversible pulpitis using two anesthetic solutions of prilocaine and mepivacaine. Materials and Methods: The current randomized controlled clinical trial was conducted on 100 patients in two groups (n = 50). Standard injection of IAN block (IANB) was performed using two cartridges of 3% mepivacaine plain in the first group and using two cartridges of 3% prilocaine with 0.03 IU felypressin in the second group. Fifteen minutes after injection, the patients were asked about lip anesthesia. In case of a positive answer, the tooth was isolated with a rubber dam. Success was defined as no or mild pain on the basis of the visual analog scale recording upon access cavity preparation, entry into the pulp chamber, and initial instrumentation. Data were analyzed with SPSS 17 using the Chi-square test, and P < 0.05 was set as statistically significant. Results: The patients' pain severities during the three stages were significantly different (P = 0.001, 0.0001, and 0.001, respectively). The success rate of IANB during access cavity preparation was 88% with prilocaine and 68% with mepivacaine. This rate during entry into the pulp chamber was 78% and 24%, respectively, which was 3.25 times higher with prilocaine than mepivacaine. The success rates during instrumentation were 32% and 10%, respectively, which was 3.2 times higher with prilocaine than mepivacaine. Conclusion: The success rate of IANB in the teeth with symptomatic irreversible pulpitis was higher using 3% prilocaine with felypressin than using 3% mepivacaine.